2022
DOI: 10.1111/bcp.15312
|View full text |Cite
|
Sign up to set email alerts
|

Fully independent validation and updating of a clinical pharmacy prioritizing risk score in an infectious disease hospital ward

Abstract: The aim of this study was to validate and update the risk score originally developed at Hospital de Clínicas de Porto Alegre, verifying its performance in an infectious disease population.Methods: This is an observational study with consecutive selection of admission in a ward of participants with infectious diseases. Predictors were age, number of medications, intravenous drugs, potentially dangerous drugs, renal dysfunction, liver dysfunction, use of nasoenteral tube, nasogastric tube, gastrostomy feeding, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Additionally, a query was performed in the references of the seven included studies to expand the references, being identified and including four more articles in this study. After reading the eleven articles included in the study (Audurier et al, 2021;dos Santos Barreto et al, 2022;Geeson et al, 2019;Mahony et al, 2018;Falconer et al, 2018;Lima et al, 2020;Mongaret et al, 2018;Gwynn et al, 2019;Falconer et al, 2020;Parekh et al, 2020;Ferrández et al, 2018), the variables of the final scores for each article were extracted and analyzed. Duplicates and items not related to pharmaceutical evaluation were excluded during this process.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a query was performed in the references of the seven included studies to expand the references, being identified and including four more articles in this study. After reading the eleven articles included in the study (Audurier et al, 2021;dos Santos Barreto et al, 2022;Geeson et al, 2019;Mahony et al, 2018;Falconer et al, 2018;Lima et al, 2020;Mongaret et al, 2018;Gwynn et al, 2019;Falconer et al, 2020;Parekh et al, 2020;Ferrández et al, 2018), the variables of the final scores for each article were extracted and analyzed. Duplicates and items not related to pharmaceutical evaluation were excluded during this process.…”
Section: Resultsmentioning
confidence: 99%